Functional Au nanoparticles for engineering and long-term CT imaging tracking of mesenchymal stem cells in idiopathic pulmonary fibrosis treatment. (September 2022) - Bao, Hongying; Cheng, Shengnan; Li, Xiaodi; Li, Yuxuan; Yu, Chenggong; Huang, Jie; Zhang, Zhijun
Abstract: Idiopathic pulmonary fibrosis (IPF) therapy has always been a big and long-standing challenge in clinical practice due to the lack of miraculous medicine. Mesenchymal stem cells (MSCs)-based therapy has recently emerged as a promising candidate for redefining IPF therapy. Enhancing the therapeutic efficacy of MSCs and understanding of their growth, migration and differentiation in harsh lung microenviroments are two keys to improving the stem cell-based IPF treatment. Herein, a non-viral dual-functional nanocarrier is fabricated by a one-pot approach, using protamine sulfate stabilized Au nanoparticles (AuPS), to genetically engineer MSCs for simultaneous IPF treatment and monitoring the biological behavior of the MSCs. AuPS exhibits superior cellular uptake ability, which results in efficient genetic engineering of MSCs to overexpress hepatocyte growth factor for enhanced IPF therapy. In parallel, the intracellular accumulation of AuPS improves the CT imaging contrast of MSCs, allowing visual tracking of the therapeutic engineered MSCs up to 48 days. Overall, this work has described for the first time a novel strategy for enhanced therapeutic efficacy and long-term CT imaging tracking of transplanted MSCs in IPF therapy, providing great prospect for stem cell therapy of lung disease.